Phospholipase D activation is functionally linked to superoxide generation in the human neutrophil. - Bonser, R W (1989)
Neutrophils stimulated with formylmethionyl-leucylphenylalanine (fMet-Leu-Phe) in the presence of butanol and ethanol formed phosphatidyl alcohols through a phospholipase D mechanism. The alcohols inhibited phosphatidic acid and diradylglycerol (DRG) formation, but did not block inositol 1, 4, 5-trisphosphate release. fMet-Leu-Phe-stimulated superoxide production was inhibited by alcohol concentrations which blocked DRG formation, whereas opsonized-zymosan-stimulated superoxide production was only partially decreased. These results suggest that phospholipase D activation is functionally linked to superoxide production in the human neutrophil.